The Characteristics of the First Kind of Chebyshev Polynomials and its Relationship to the Ordinary Polynomials - Maulidi, Ikhsan; Wibowo, Bonno Andri; Apriliani, Vina; Umam, Rofiqul (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
In this article, we discuss the Chebyshev Polynomial and its characteristics. The second order difference equation and the process obtaining the explicit solution of the Chebyshev polynomial have been given for each real number. The symmetry and orthogonality of the Chebyshev polynomial has also been demonstrated using the explicit solutions obtained. Furthermore, we have also given how to approx the polynomial function using the Chebyshev polynomials.